KAJIAN KONSENTRASI INOKULUM RAGI TERHADAP SIFAT KIMIA DAN BAKTERI ASAM LAKTAT TEMPE KACANG GUDE (Cajanus cajan, L) (Studi on Chemical Properties Yeast Inoculum Concentration and Lactid Acid Bacteria of Pigeonpea Tempeh): Suparno1), Kusumadati, W.1), Giyanto1), Winerungan, S.A.J.1) - Administrator Journal (Fakultas Pertanian Universitas Palangka Raya, 2018)
ABSTRACTGenerally, tempeh is made from soybean, but low production of soybean in Indonesia bringing ongovernment have to import its. Soybean import 70% approximated from United State constitutetransgenic soybean which apprehensived have negative effect for health. Indonesia has so manylocal legume such as pigeon pea (Cajanus cajan (L.) Millsp.). That could be used as soy beansubstitute as raw material of tempeh. This study aimed to determine the effect of inoculumconcentration pigeonpea beans right to quality and chemical properties of lactid acid bacteriatempeh produced during the fermentation proces. It can be concluded that the inoculumconcentration of 2,50 g/kg of material, can increase levels of the amino nitrogen of 1,582 %, andcan inhibit the growth of lactid acid bacteria. It is also recommended for further research conducedon the long soaking, soaking place, and fermentation time is right to improve the quality ofpigeonpea beans tempeh produced.Keywords : Concentration of the inoculum, lactid acid bacteria, and tempeh pigeonpea